Making a green machine : the infrastructure of beverage container recycling - Jørgensen, Finn Arne, 1975- (Studies in modern science, technology, and the environment., 2011)
"Making a Green Machine examines the development of the Scandinavian beverage container deposit-refund system, which has the highest return rates in the world, from 1970 to present. Finn Arne Jorgensen's comparative framework charts the complex network of business and political actors involved in the development of the reverse vending machine (RVM) and bottle deposit legislation to better understand the different historical trajectories empty beverage containers have taken across markets, including the U.S. The RVM began simply as a tool for grocers who had to handle empty refillable glass bottles, but has become a green machine to redeem the empty beverage container, helping both business and consumers participate in environmental actions"--Provided by publisher.